Implementasi Konseling Individu Dengan Teknik Self Management Untuk Meningkatkan Kemampuan Mengatur Waktu - Faizah, Umi; Ulwiyah, Imaratul; Romika Mawaddati, Ika (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2026)
The problem found at SMK Abdul Aziz is that some students have low time management skills such as arriving late to school, rarely submitting school assignments, running away from the boarding school because of difficulties in balancing study time, boarding school activities and break time. The existence of this phenomenon, the purpose of the study is to improve time management skills through individual counseling with Self-management techniques. The research method uses a Single-Case Experimental Design approach with an A-B pattern. Respondents numbered 30 students, with 2 samples selected by purposive sampling. Data collection methods were observation, interviews and questionnaires. Statistically, the results of the study were analyzed using the Wilcoxon Signed Rank Test using SPSS 23 for the MG score: Z value = -2.060 and Asymp. Sig. (2-tailed) = 0.039 <0.05. can be interpreted because the significance value is <0.05, so there is a significant difference between students' time management skills before and after the intervention. Likewise, the results of the NF study: Z value = -2.041 and Asymp. Sig. (2-tailed) = 0.041< 0.05. This means that individual counseling services using self-management techniques can improve the time management skills of class XB students. Keywords: Individual Counseling, Self-Management, Time Management.